2020
DOI: 10.4103/ija.ija_974_19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ondansetron administration 20 minutes prior to spinal anaesthesia on haemodynamic status in patients undergoing elective caesarean section: A comparison between two different doses

Abstract: Background and Aims: Spinal anaesthesia is currently the most common method used for managing patients undergoing elective caesarean sections. Recent meta-analyses have been supporting the use of 5-HT3 antagonists, like ondansetron, to attenuate hypotension induced by spinal block. Various doses of ondansetron were given intravenously five minutes before spinal block. However, a consensus on definitive dose and timing for maximal benefit is yet to be agreed upon. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These findings are consistent with those made by Sahoo et al (7) who had 4 mg of ondansetron, given 5 minutes prior to spinal anesthesia for a caesarean section delivery, Trabelsi et al (2) In comparison to the control group, they found that patients who took ondansetron (5 mg) had higher SBP, DBP, and MAP. Also, Samarah et al (9) researchers tested a novel strategy by giving intravenous ondansetron 20 minutes before to spinal anesthesia, and they found no discernible change in blood pressure readings across the trial groups (P>0.05). This discrepancy with the current study may be due to the difference in the type of surgery and population in the first study and the timing difference in the second as mentioned before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those made by Sahoo et al (7) who had 4 mg of ondansetron, given 5 minutes prior to spinal anesthesia for a caesarean section delivery, Trabelsi et al (2) In comparison to the control group, they found that patients who took ondansetron (5 mg) had higher SBP, DBP, and MAP. Also, Samarah et al (9) researchers tested a novel strategy by giving intravenous ondansetron 20 minutes before to spinal anesthesia, and they found no discernible change in blood pressure readings across the trial groups (P>0.05). This discrepancy with the current study may be due to the difference in the type of surgery and population in the first study and the timing difference in the second as mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Samarah et al (9) discovered that ondansetron prevented hypotension in caesareansurgery patients who were pregnant, but the impact was not superior to that of vasoconstrictors.…”
Section: Discussionmentioning
confidence: 99%
“…This study sheds light on the available evidence on this topic to this date. Prior studies have explored the use of ondansetron on the risk of incident hypotension and bradycardia and reported that this medication does not provide clinical benefit [10][11][12][13] . Meta-analysis performed by Chengmao Zhou et al 14 with 21 randomized controlled trials found no statistically difference in hypotensive events between groups.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Previous studies tried to demonstrate that administration of ondansetron, a potent and highly selective 5-HT3 receptor antagonist, minutes before spinal anesthesia could attenuate hypotension and bradycardia. While a few studies showed that ondansetron administration might be beneficial [7][8][9] , most have shown evidence of little or no protection [10][11][12][13][14] . Small sample sizes, differences in the administration of co-interventions (e.g., pre-loading/co-loading fluids) and heterogeneity in the definitions of hypotension might be some of the causes for this discrepancy.…”
Section: Introductionmentioning
confidence: 99%